Groundwater recharge pathway according to the environmental isotope: the case of Changwu area, Yangtze River Delta Region of China. Issue 3 (7th December 2021) - He, Liang; Zhang, Junru; Chen, Suozhong; Hou, Manqing; Chen, Junyi
Abstract: Groundwater recharge is an important factor affecting water circulation. As groundwater has slow seepage, directly observing the seepage velocity and recharge path of groundwater in the aquifer is difficult. Environmental isotope technology has become an important means to clarify the mechanism of groundwater movement and the mechanism by which groundwater recharges from the micro and macro perspectives. The Changwu area of Jiangsu Province was taken as an example to identify the recharge sources of groundwater and the recharge paths of groundwater and surface water by using the measured data of isotopes D, 18 O, 34 S, and T. The results indicated that the shallow aquifer and the I confined aquifer in the Changwu area are mainly recharged by precipitation and surface lake water. The II confined aquifer along the Yangtze River is recharged by modern precipitation. Moreover, the II confined aquifer in the Henglin area was recharged by the ancient Yangtze River before 4, 000 years ago, and no recharge relationship exists now. the recharge condition of the II confined aquifer around the northwest of Gehu Lake is in the climate environment of 8, 000 years ago and was caused by the surface depression lake water at that time. Additionally, the concealed limestone aquifer is primarily supplied by the II confined aquifer, while the concealed sandstone aquifer supplies the II confined aquifer. Hence, to find out the recharge conditions of groundwater aquifers based on the environmental isotope is conducive to scientific and reasonable evaluation of groundwater resources and to ensure the sustainable development and utilization of groundwater resources. HIGHLIGHTS: Environmental isotope technology can elucidate the mechanism of groundwater movement and groundwater recharge. The isotopic concentration of groundwater generally reveals the weighted average of precipitation in the recharge area. The isotopic signatures preserved in the groundwater system are influenced by the geological setting and the hydrodynamic dispersion. Graphical Abstract